Benny and Penny in Just pretend : a toon book - Hayes, Geoffrey (New York : Toon Books, 2008)
Annoyed with his little sister who always wants to play pretend with him, Benny intentionally loses her, but soon feels bad after she is gone.
Book Links (A.L.A.)
School Library Journal
Wilson's Children
Book Links (A.L.A.), October 2010
Booklist starred, March 2008
Bulletin (Center for Children's books), July 2008
Keywords: Brothers and sisters -- Comic books, strips, etc -- Juvenile fiction; Courage -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Brothers and sisters -- Fiction; Cartoons and comics; Courage -- Fiction; Mice -- Fiction; Comic books, strips, etc; Courage -- Comic books, strips, etc -- Fiction; Graphic novels; Mice -- Comic books, strips, etc -- Fiction; Siblings -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Graphic novels